2022
DOI: 10.1038/s41598-022-24876-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of 3D-Slicer + 3D printing guide combined with transcranial neuroendoscopic in minimally invasive neurosurgery

Abstract: To explore the clinical advantages of 3D-Slicer + 3D printing guide combined with transcranial neuroendoscopic in minimally invasive neurosurgery. By collecting the datum of patients who underwent craniotomy under 3D-Slicer + 3D printing guide plate positioning combined with transcranial neuroendoscopic in our hospital from October 2021 to February 2022, this paper introduces the accurate planning and positioning lesions of patients before operation and the minimally invasive operation of intraoperative neuroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…An article published in 2021, which included 13 patients with meningioma, reported that 3D printing technology was helpful for the accurate location of meningioma before operation 20 . Another article published in 2022 found that 3D slicer + 3D printing guide technology could accurately locate the intracranial lesions, and this study included 6 patients with brain tumors 21 .…”
Section: Discussionmentioning
confidence: 99%
“…An article published in 2021, which included 13 patients with meningioma, reported that 3D printing technology was helpful for the accurate location of meningioma before operation 20 . Another article published in 2022 found that 3D slicer + 3D printing guide technology could accurately locate the intracranial lesions, and this study included 6 patients with brain tumors 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial neuroendoscope minimally invasive surgery technology, using the advantages of neuroendoscope such as good light, flexible freedom, and close observation, has natural advantages in intracerebral hemorrhage surgery [ [8] , [9] , [10] ]. It is undoubtedly the best choice to cooperate with our team's newly developed 3D slicer reconstruction and precise positioning system [ 11 , 12 ]. In this case, we preliminarily decided to choose the frontal horn approach of lateral ventricle to clear the intraventricular hematoma according to the cerebral CT results of the patient in the external hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial neuroendoscopic minimally invasive surgery has the advantages of good light, flexible freedom, and close observation. Combined with 3D slicer reconstruction and precise positioning system [ 11 , 12 ], it may be a good choice for the treatment of distal terminal artery aneurysms that lack collateral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it supports extensions, with over a hundred open-source extensions available on the platform. These extensions range from radiomics analysis [10,11] to artificial intelligence (AI)-based automatic organ segmentation for medical image analysis [12,13] and from surgical navigation [14,15] to target delineation [16,17] and dose calculation for radiation therapy clinical tools [18,19]. Its extensive functionality surpasses that of professional workstations utilized in clinical environments [20][21][22][23][24].…”
Section: Application Of 3d Slicer Platform In Medical Image Analysismentioning
confidence: 99%